2015
DOI: 10.1007/s11665-015-1693-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ce Addition on High Temperature Deformation Behavior of Cu-Cr-Zr Alloys

Abstract: Hot deformation behavior of the Cu-Cr-Zr and Cu-Cr-Zr-Ce alloys was investigated by compressive tests using the Glee-ble-1500D thermomechanical simulator at 650-850°C and 0.001-10 s 21 strain rate. The flow stress decreased with the deformation temperature at a given stain rate. However, the flow stress increased with the strain rate at the same deformation temperature. The constitutive equations for two kinds of alloys were obtained by correlating the flow stress, the strain rate and temperature using stepwis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 19 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…Ji et al 11 found that under the test condition the deformation activation energy of the Cu-0.36Cr-0.03Zr alloy was 432.6 kJ/mol, and an experimentally based constitutive model was developed to predict the flow stress of the alloy during high temperature deformation. Zhang et al 12 found that the addition of Ce can improve the Cu-Cr-Zr alloy deformation activation energy during hot deformation. However, relations between the important points of the flow stress curves and the critical conditions for DRX initiation during hot working need further attention.…”
Section: Introductionmentioning
confidence: 99%
“…Ji et al 11 found that under the test condition the deformation activation energy of the Cu-0.36Cr-0.03Zr alloy was 432.6 kJ/mol, and an experimentally based constitutive model was developed to predict the flow stress of the alloy during high temperature deformation. Zhang et al 12 found that the addition of Ce can improve the Cu-Cr-Zr alloy deformation activation energy during hot deformation. However, relations between the important points of the flow stress curves and the critical conditions for DRX initiation during hot working need further attention.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the activation energy Q of the Cu-Cr-Zr with that in Ref. [10], the Q increased by 21% with the addition of Ce. The reason is that the Ce can fix dislocations at the grain boundary and maintain high dislocation density.…”
Section: Activation Energy and Constitutive Equationsmentioning
confidence: 83%
“…Many investigations of the alloys hot deformation processing have been carried out. Zhang et al [10] found that the addition of Ce can improve the deformation activation energy of the Cu- 0.4Cr-0.1Zr alloy during hot deformation. Ji et al [11] found that the activation energy of the Cu-0.36Cr-0.03Zr alloy was 432.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [11] researched the aging behavior of the Cu-0.4Cr-0.15Zr-0.05Ce (wt%) alloy and obtained a hardness of 183 HV with electrical conductivity reaching up to 83% IACS. [23] However, these studies are limited to aging precipitation behavior, and very few literature reports of the RE studies focus on hot deformation behavior. In general, this Cu-Zr alloy has high strength, high softening temperature, and perfect wear performance.…”
Section: Introductionmentioning
confidence: 99%